2021
DOI: 10.18502/ijhoscr.v15i1.5244
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Pre-Storage Irradiation Blood on Quality of Red Blood Cells

Abstract: Background: Irradiation leads to increased storage lesions that may have harmful effects if transfused. Various storage lesions research has been carried out, and only very few articles are available on the impact of gamma irradiation on RBC storage lesions. Since there has been no study about finding the best time for irradiation, we decided to investigate the effect of irradiation on Red blood cells at different storage times after blood collection Materials and Methods: A total of 40 units of red bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…They also pointed out that the blood unit should be transfused as soon as possible after the irradiation. [ 10 ] Results in our study showed the changes in various biochemical parameters during different days of the storage period. It is seen that plasma potassium, lactate, and LDH levels gradually increased during the storage period, whereas sodium and glucose levels decreased significantly over time.…”
Section: Discussionmentioning
confidence: 60%
“…They also pointed out that the blood unit should be transfused as soon as possible after the irradiation. [ 10 ] Results in our study showed the changes in various biochemical parameters during different days of the storage period. It is seen that plasma potassium, lactate, and LDH levels gradually increased during the storage period, whereas sodium and glucose levels decreased significantly over time.…”
Section: Discussionmentioning
confidence: 60%
“…Irradiation has considerable effects on unit stability during storage. 18,19 We, therefore, included both irradiated and non-irradiated units in our study (6 of each). Importantly, because we sampled the units at multiple time points during the first 24 h post-washing this allowed for a unique analysis of the effects of irradiation during this critical interval.…”
Section: Discussionmentioning
confidence: 99%
“…Irradiation has considerable effects on unit stability during storage 18,19 . We, therefore, included both irradiated and non‐irradiated units in our study (6 of each).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations